Good faith and fair dealing in hire purchase contract : a study on the Islamic and conventional practice in Malaysia - Nurhidayah bt. Abdullah (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2005)
This study examines and analyzes the important of the element of good faith and fair dealing in a hire purchase contract. A hire purchase contract is a contract whereby one party, called "the owner", lets goods on "hire" to another party the "hirer", and agrees that the hirer may at his own option, return the goods when he no longer needs them or terminates the hire on completion of the necessary payments agreed in the contract. Good faith is a principle derived from the rules ''pacta sunt servanda" and other legal rules distinctively and directly related to honesty, fairness and reasonableness. The application of good faith is determined at a particular time by the standard of honesty, fairness and reasonableness prevailing in the communities which are considered appropriate for formulation in new revised legal rules In the 18th century, the concept of fair dealing is an essential concept supporting an efficient and emerged as a governing principle applicable to all Common Law contracts. However, later, the element of good faith was confined mainly to insurance contract. Under the Islamic law, the element of good faith (Ihsan) and fair dealing (Ad[) are important and highly emphasized. Furthermore, in Islam, the moral criteria for the legality of any act and honesty of a merchant are clearly imposed as a basis of commercial activity. All bad practices are condemned. One of the conclusion made in this research, is that good faith and fair dealing are two crucial elements in hire purchase contracts both in the conventional and Islamic systems. This is because the attributes of honesty, reasonableness and fairness should be the underlying principles in every distinct hire purchase contract to connote the notion of "fair dealing" transaction whereby the contract's sanctity is performed thus satisfying the demand of the parties in the contract. The research methodology applied in this research is mainly library research. However, it also includes field study in the form of interviews with respective officers of selected banks in Malaysia which offer both Islamic and conventional hire purchase financing. The law in this research is stated as at 30th April 2005.